Pola Hidup Sederhana dalam Perspektif Hadis di Era Konsumtif - Mila Amelia; Zaenal Abidin; Muhammad Alif (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2024)
Lifestyle is currently one of the main highlights, many people adopt a consumptive or excessive lifestyle. This research aims to discuss a simple lifestyle based on hadith. This research uses a type of qualitative research, namely the hadith thematic method. The formal object of this research is the understanding and urgency of a simple lifestyle which is grouped based on hadith themes. Meanwhile, the material objects in this research are a simple lifestyle and consumer behavior. The discussion in this research explains that a good life is a life that applies simplicity. The conclusion of this research is that a simple lifestyle is highly recommended by the Prophet and Allah does not like people who behave consumptive or wasteful. By behaving simply, you will get many benefits.